Controlling the distance of highly confined droplets in a capillary by interfacial tension for merging on-demand. Issue 1 (28th November 2018) - Ferraro, D.; Serra, M.; Filippi, D.; Zago, L.; Guglielmin, E.; Pierno, M.; Descroix, S.; Viovy, J.-L.; Mistura, G.
Abstract : Confined droplet speed and distance control devoted to merging-on-demand in a uniform cross-section microchannel, based on interfacial tension difference and suitable for enzymatic reaction investigations. Abstract : Droplet microfluidics is a powerful technology that finds many applications in chemistry and biomedicine. Among different configurations, droplets confined in a capillary (or plugs) present a number of advantages: they allow positional identification and simplify the integration of complex multi-steps protocols. However, these protocols rely on the control of droplet speed, which is affected by a complex and still debated interplay of various physico-chemical parameters like droplet length, viscosity ratio between droplets and carrier fluid, flow rate and interfacial tension. We present here a systematic investigation of the droplet speed as a function of their length and interfacial tension, and propose a novel, simple and robust methodology to control the relative distance between consecutive droplets flowing in microfluidic channels through the addition of surfactants either into the dispersed and/or into the continuous phases. As a proof of concept application, we present the possibility to accurately trigger in space and time the merging of two confined droplets flowing in a uniform cross-section circular capillary. This approach is further validated by monitoring a conventional enzymatic reaction used to quantify the concentration of H2 O2 in a biological sample, showing its potentialities in both continuous and stopped assay methods.